Soil Fertility and Leaf Nutrient Status of Mango Orchard Sites (Dhaka University Journal of Biological Sciences, 2020)
Twenty soil and leaf samples from 20 orchards of mango (Mangifera indica L.) were collected from different locations of Rajshahi and Satkhira regions to evaluate soil texture, pH, organic matter, available and total nitrogen, phosphorus, potassium and sulfur of soils and the concentration of N and K in mango leaves. The pH of the soil varied from 6.3 - 7.9 and organic matter content varied from 0.72 - 3.60 per cent. The available nitrogen, phosphorus, potassium, and sulfur of the soils ranged from 190 - 510, 39 - 196, 36 - 206 and 25 - 235 mg/kg, respectively. The values of total N, P, K and S were 0.03 - 0.12, 0.022 - 0.210, 0.235 - 0.0.936 and 0.005 - 0.266 per cent, respectively. The dominant soil textural class was silty clay loam. The mean concentration of nitrogen (0.88%) and potassium (0.61%) in the leaf sample was low. The overall fertility status of the soils of Rajshahi and Satkhira regions in relation to mango cultivation is moderate.Dhaka Univ. J. Biol. Sci. 29(2): 155-163, 2020 (July)